EVALUATION OF COMPARATIVE EFFICACY OF NEELKANTHI (AJUGA BRACTEOSA), TEJAPATRA (CINNAMOMUM TAMALA) AND METHIKA BEEJA (TRIGONELLA FOENUM GRAECUM) CHURNA IN THE MANAGEMENT OF DIABETES MELLITUS - Chaudhary, Vijay; Johri, Sharad; Kumar Rana, Ashwani (International Journal of Ayurveda and Pharma Research, 2015)
Introduction: Diabetes mellitus is a disease since antiquity. It is emerging as a pandemic in the society. Though a lot of potent antidiabetic drugs are available today but none of them is free from untoward effects. A number of Ayurvedic herbal drugs are effective in the management of diabetes mellitus. But most of these drugs are required to be taken in bulk invariably for long span hence some time their poor palatability becomes a big problem. Moreover which herbal is more potent and in which particular situation it is more suitable also needs to be evaluated. Objective: This study was conducted to clinically evaluate comparative efficacy of Neelkanthi Churna, Tejapatra and Methika Beeja Churna in the management of diabetes mellitus. Materials and Methods: The study was conducted as a part of post graduate thesis research work. Total 45 patients of diabetes mellitus were registered in the present clinical study and they were administered trial drugs for the duration of 45 days. Registered patients were randomly divided into two groups. In group-I patients were managed with Tejapatra and Methika Beeja Churna. Group-II patients were managed with Neelkanthi Churna. Observations and conclusion: Patients were thoroughly assessed on various parameters during complete trial period. Though both Churna of Neelkanthi and Churna of Tejapatra and Methika Beeja were found significantly effective in the management of Madhumeha but Churna of Neelkanthi showed definitely better effect on various subjective, objective and biochemical parameters. No untoward effect was noticed during treatment and follow up period.